Responsive teaching for sustainable learning : a framework for inclusive education - Berman, Jeanette; Graham, Lorraine; Bellert, Anne.; McKay-Brown, Lisa. (b, 2024)
"Drawing on Australian and international research, this book presents teaching and support strategies for educators to be responsive to the particular learning needs of each of their students and deliver quality inclusive education in a sustainable way. Based on the Responsive Teaching Framework, an instructionally-focused approach for teaching that is evidence-based, purposeful and responsive to students' learning needs, this book assists teachers to build on their current capabilities and strengthen their expertise to ensure that every student in their classrooms can be an effective learner. Part 1 of the book explains the theoretical and practical basis of the Sustainable Learning approach as a way of thinking about inclusive education through a focus on responsive teaching. Part 2 unpacks each of the eight steps of the Responsive Teaching Framework. These chapters focus on the reflective questions that guide responsive practice, from whole class and individual student perspectives, outlining practical strategies that can be used, as well as the assessment practices and evidence-gathering needed to support each step of the responsive teaching process. Written for practicing educators, school leaders and postgraduate students, Responsive Teaching for Sustainable Learning delivers models for inclusive, sustainable teaching practice in an easily accessible format"--
Includes bibliographical references and index.
Keywords: Inclusive education -- Australia; Student-centered learning -- Australia; Reflective learning -- Australia